Kepemimpinan dan Pengambilan Musyawarah dalam Manajemen Pesantren: Analisis Proses Keputusan di Pesantren Terpadu Serambi Mekkah Padang Panjang - Yudo, Yudo; Damri, Damri; Asmendri, Asmendri; Sari, Milya (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the deliberative decision-making process in the management of the Integrated Boarding School Serambi Mekkah Padang Panjang. The method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies. Data analysis is conducted thematically, by filtering and grouping the data obtained from observations and documentation based on the main themes relevant to the research objectives. The findings reveal that musyawarah at Serambi Mekkah is not merely a cultural practice, but an institutionalized decision-making mechanism, manifested in leadership meetings, teacher forums, and parent assemblies. The decision-making process is participatory, involving various stakeholders and reflecting values such as collectivity, openness, and shared responsibility. Islamic principles such as trust (amanah), justice (‘adl), and mutual respect form the foundation of this process. However, certain challenges persist, including dominant leadership figures, time constraints, and limited managerial capacity among some participants. This article asserts that musyawarah is not just a tradition, but an effective and relevant management system for Islamic educational institutions.